One‐step synthesis of hydrophilic graphene‐Fe3O4‐PVA composite film: Micromorphology and performance. Issue 44 (27th June 2019) - Wang, Pengjun; Zhang, Mengyi; Liu, Yang; Wang, Liqiu; Lv, Qiulan; Xu, Daxing; Liu, Xiu; Wang, Guangtao; Yang, Wan; Wang, Pengchen; Yu, Tengbo; Xing, Shichao
ABSTRACT: Multifunctional polymers have wide applications in smart materials. In this study, the multifunctional polymer (hydrophilic graphene‐Fe3 O4 ‐PVA, GFP composite films) were synthesized by mixing with hydrophilic graphene (HG), ferrous ammonium sulfate, and ferric chloride in PVA solution through one‐pot coprecipitation method. GFP composite films were characterized by XRD, FT‐IR. Their morphology and particle size of Fe3 O4 in GFP composite film were observed by TEM, SEM, and AFM. The results indicated that the morphology of Fe3 O4 in GFP could be modulated from sphere shape to rod structure by the loading quantity of HG. Besides, many properties of GFP composite films were investigated. Firstly, GFP composite films demonstrated the fast magnetic response and high thermal stability. Secondly, the introduction of HG not only simultaneously enhanced the stiffness and ductility of GFP composite films, but also improved their flame retarding performance. Finally, HG regulating effect for the morphology of Fe3 O4 in GFP and improvement mechanism of HG for mechanical performance of GFP composite films were illustrated. Both of them might be contributed to the hydrogen bonds effect among Fe3 O4, PVA, and HG. Thus, these multifunctional GFP composite films can be applicable as the basis of fabricating smart materials in different fields. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48174. Abstract : GFP composite films exhibited the excellent regulation for the morphology of Fe3 O4 particles, the quick ferromagneticresponse, the higher thermal stability, mechanical and flame‐retarding properties.